Biomarker Discovery by Novel Sensors Based on Nanoproteomics Approaches - Dasilva, Noelia (Molecular Diversity Preservation International (MDPI), 2012)
During the last years, proteomics has facilitated biomarker discovery by coupling high-throughput techniques with novel nanosensors. In the present review, we focus on the study of label-based and label-free detection systems, as well as nanotechnology approaches, indicating their advantages and applications in biomarker discovery. In addition, several disease biomarkers are shown in order to display the clinical importance of the improvement of sensitivity and selectivity by using nanoproteomics approaches as novel sensors.